Hubungan Dukungan Sosial dengan Problematic Internet Use pada Mahasiswa Pengguna Media Sosial - Annisa Nur Octaviani; Siti Qodariah (UNISBA Press, 2022)
Abstract. Undergraduates use the internet for academic and personal purposes, however, excessive use of the internet causes various negative consequences for the user. One of the groups that is at risk for problematic internet use is those who seek social support on the internet because they perceive that they lack social support in the real world. The behavior of seeking support on the internet leads to symptoms of problematic internet use. Therefore, this study aims to determine the relationship between perceived social support and problematic internet use. This research was conducted using a quantitative approach with Spearman's Rank correlation analysis technique. Data was collected using accidental sampling technique and obtained 651 college students who use social media in Bandung. Multidimensional Scale of Perceived Social Support (MSPSS) is used to measure perceived social support and Generalized Problematic Internet Use 2 (GPIUS-2) is used to measure problematic internet use, both of them have been adapted into Bahasa Indonesia. The results showed a correlation coefficient of -.459 which indicates a strong negative relationship between social support and problematic internet use. That means, the lower the perception of social support, the higher the problematic internet use. Abstrak. Mahasiswa menggunakan internet untuk kepentingan akademik maupun pribadi, kendati demikian, penggunaan internet yang berlebihan dapat memberikan berbagai dampak negatif bagi penggunanya. Salah satu kelompok yang paling berisiko ialah individu yang mencari dukungan di internet karena merasa kurang memiliki dukungan sosial. Perilaku mencari dukungan di internet mengarahkan gejala-gejala dari problematic internet use. Oleh karena itu, penelitian ini bertujuan untuk mengetahui keeratan hubungan dukungan sosial dengan problematic internet use. Penelitian dilakukan menggunakan pendekatan kuantitatif dengan teknik analisis korelasi Rank Spearman. Pengumpulan data dilakukan dengan teknik accidental sampling dan diperoleh sebanyak 651 mahasiswa pengguna media sosial di Kota Bandung. Digunakan Multidimensional Scale of Perceived Social Support (MSPSS) untuk mengukur dukungan sosial dan Generalized Problematic Internet Use Scale 2 (GPIUS-2) untuk mengukur problematic internet use, dimana kedua alat ukur tersebut telah diadaptasi ke dalam Bahasa Indonesia. Hasil penelitian menunjukkan nilai koefisien korelasi sebesar -.459 yang mengindikasikan adanya hubungan negatif yang cukup kuat antara dukungan sosial dengan problematic internet use. Semakin rendah dukungan sosial, maka semakin tinggi problematic internet use.